Prevalence of Iron-Deficiency Anemia in Infants Living in Rural Areas and the Factors that Influence it in the Pandemic COVID-19 Era - Ringoringo, Harapan Parlindungan; Natalia, Imanuella Yessy; Panghiyangani, Roselina; Hartoyo, Edi; Lao, Rahmiati (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Iron-deficiency anemia (IDA) is caused by inadequate intake of iron or impaired erythrocyte formation due to chronic blood loss. AIM: This study aimed to obtain data on the prevalence of iron deficiency and IDA in the pandemic COVID-19 era and to investigate the relationship of infant nutritional status, maternal education, maternal occupation, maternal parity, and family income with the prevalence of iron deficiency and IDA in infants 9–12 months at the Cempaka Banjarbaru Community Health Center. METHODS: A cross-sectional analytic descriptive approach was used with a consecutive sampling technique to conduct this study. The sample consisted of 50 infants between 9 and 12 months old that had completed blood count and peripheral blood smear at measles immunization in May–September 2020 at the Cempaka Banjarbaru Community Health Center. RESULTS: The results showed that the prevalence of iron deficiency, IDA, and hemolytic anemia was 16%, 28%, and 22%, respectively. Meanwhile, the data analysis was conducted using Chi-square and Fisher’s exact test. The results showed a significant relationship between family income factors and the prevalence of iron deficiency and IDA (p = 0.023). CONCLUSION: Infants at the age of 9–12 months need to have a complete blood count examination to detect an earlier iron deficiency and IDA.